KENDALA GURU BK DALAM IMPLEMENTASI KURIKULUM 2013 DI KELAS X SMK NEGERI 4 PADANG - Yelfita, Zulni - (Bimbingan dan Konseling, 2014)
Background of this research was unpreparedness of counselor in implementing service of guidance and counseling based on petition curriculum 2013 not yet same toward condition actually. The aim of this research was to find out obstacle counselor in implementing of curriculum 2013. It showed from design, implementation and program evaluation. Kinds of this reasearch is a qualitative descriptive. The informant of this research were third counselor, representative of curricullum and headmaster. In this research, the researcher used interview and documentation. The data of this research tested with used trianggulasi, membercheck, and technique from reduction the data, presenting the data and conclusion. The results of this research showed that counselor obstacle to made guidance and counseling program The counselor was not being trained and lack of implementing in program counselor. Because limited of counselor,lack of time toward classical guidance,counseling service, program evaluation counselor still restricted in making insrument and counselor have difficult to evaluate the students in long time.